Clinical Improvement of Severe Chronic Acne Conglobata. Case Report. (Ozone Therapy Global Journal, 2018)
Chronic severe acne conglobata is a severe form of acne presenting with multiple deep abscesses.  It is frequently a debilitating and painful condition.  Treatment options include long-term systemic antibiotics, intralesional steroid injections, systemic retinoids, systemic steroids, adalimubab, electron beam radiation, and topical treatment.1  These treatments frequently lack efficacy and may have risks of significant side effects.   Ozone therapy has been used successfully in treating acne and cysts.  A 34 year-old white male presented with chronic, large, numerous, painful draining cysts of the trunk, groin and neck of ten years duration.  The patient reported excessive alcohol ingestion and suicidal thoughts due to the pain.  Past treatments with antibiotics and steroids were unsuccessful.  During a period of one year the patient was treated with ozone: topical ozonated oil, full-body bag topical ozone, intralesional ozone, and ozone minor autohemotherapy. The patient reports a reduction in the number of daily lesions, reduction in pain, reduction in lesion drainage, decreased lesion resolution, an optimistic life outlook, and reduction of alcohol intake.  The success of ozone therapy in this case indicates ozone therapy is a safe and effective option for patients with severe debilitating chronic acne conglobata.